Repulsive response of Meloidogyne incognita induced by biocontrol bacteria and its effect on interspecific interactions - Zhao, Yanli; Zhou, Qinying; Zou, Chenggang; Zhang, Keqin; Huang, Xiaowei (Frontiers in Microbiology, 2022)
The aversive behavior of Caenorhabditis elegans is an important strategy that increases their survival under pathogen infection, and the molecular mechanisms underlying this behavior have been described. However, whether this defensive response occurs in plant-parasitic nematodes (PPNs), which have quite different life cycles and genomic sequences from the model nematode, against biocontrol microbes and affects interspecific interactions in ecological environments remains unclear. Here, we showed that Meloidogyne incognita, one of the most common PPNs, engaged in lawn-leaving behavior in response to biocontrol bacteria such as Bacillus nematocida B16 and B. thuringiensis Bt79. Genomic analysis revealed that the key genes responsible for the aversive behavior of C. elegans, such as serotonin- and TGF-β-related genes in canonical signaling pathways, were homologous to those of M. incognita, and the similarity between these sequences ranged from 30% to 67%. Knockdown of the homologous genes impaired avoidance of M. incognita to varying degrees. Calcium ion imaging showed that the repulsive response requires the involvement of the multiple amphid neurons of M. incognita. In situ hybridization specifically localized Mi-tph-1 of the serotonin pathway to ADF/NSM neurons and Mi-dbl-1 of the TGF-β pathway to AVA neurons. Our data suggested that the repulsive response induced by different biocontrol bacteria strongly suppresses the invasion of tomato host plants by M. incognita. Overall, our study is the first to clarify the pathogen-induced repulsive response of M. incognita and elucidate its underlying molecular mechanisms. Our findings provide new insights into interspecific interactions among biocontrol bacteria, PPNs, and host plants.